Dual RNA-Seq Analysis Reveals Transcriptome Effects during the Salmon–Louse Interaction in Fish Immunized with Three Lice Vaccines - Antonio Casuso; Valentina Valenzuela-Muñoz; Cristian Gallardo-Escárate (Vaccines, 2022)
Due to the reduced efficacy of delousing drugs used for sea lice control in salmon aquaculture, fish vaccines have emerged as one of the most sustainable strategies in animal health. Herein, the availability of C. rogercresseyi and Salmo salar genomes increases the capability of identifying new candidate antigens for lice vaccines using RNA sequencing and computational tools. This study aimed to evaluate the effects of two recombinant antigens characterized as peritrophin and cathepsin proteins on the transcriptome profiling of Atlantic salmon during a sea lice infestation. Four experimental groups were used: Peritrophin, cathepsin, and peritrophin/cathepsin (P/C), and PBS as the control. C. rogercresseyi female, S. salar head kidney, and skin tissue samples were sampled at 25 days post-infestation (dpi) for Illumina sequencing and RNA-seq analysis. Differential gene expression, gene ontology, and chromosomal expression analyses were performed. Furthermore, the dual RNA-seq analysis approach was performed to simultaneously explore host and pathogen transcriptomes, identifying functional associations for vaccine design. The morphometry of female sea lice exposed to immunized fish was also evaluated. The RNA-Seq analysis exhibited prototype-dependent transcriptome modulation, showing a conspicuous competition for metal ions during the infestation. Moreover, Dual RNA-seq analysis revealed vaccine-dependent gene patterns in both the host and the pathogen. Notably, significant morphometric differences between lice collected from immunized and control fish were observed, where cathepsin and P/C showed 57% efficacy. This study showed the potential of two proteins as lice vaccines for the salmon industry, suggesting novel molecular mechanisms between host–parasite interactions.